2×N twin-field quantum key distribution network configuration based on polarization, wavelength, and time division multiplexing - Park, Chang Hoon; Woo, Min Ki; Park, Byung Kwon; Kim, Yong Su; Baek, Hyeonjun; Lee, Seung Woo; Lim, Hyang Tag; Jeon, Seung Woo; Jung, Hojoong; Kim, Sangin; Han, Sang Wook (npj Quantum Information, 2022)
Developing quantum key distribution (QKD) has been recently directed toward distance extension and network expansion for real-world secure communications. Considering a recent report on a quantum communication network over 4,600 km, it seems that QKD networks using conventional protocols have been sufficiently studied. However, although the twin-field QKD (TF-QKD) proposed for long-distance QKD has been studied deeply enough to succeed the demonstrations over 428- and 511-km deployed fibers, TF-QKD networks have been verified only for a ring network. In this work, we propose a star topological 2 × N TF-QKD network scheme, where the coherence maintenance issue, being the primary obstacle to implementing TF-QKD, can be minimized by the automatic mode-matching feature of the Sagnac-based plug-and-play architecture. A lower number of active controllers is required for our scheme in comparison with one-way TF-QKD networks. Moreover, our scheme adopts a cost-effective configuration that requires only a single pair of single-photon detectors for the entire network system. We conducted a proof-of-concept experiment over a 50-km fiber successfully, achieving an average secret key rate of 1.31 × 10−4bit per pulse (1.52 bit per second) with the finite-size effect.
Keywords: A-RINGS; Automatic mode; Communications networks; Deployed fiber; Distribution network configuration; Network expansion; Network scheme; Real-world; Ring networks; Time-division multiplexing